Validation studies of a questionnaire developed to measure students' engagement with systems thinking - Camelia, Fanny; Ferris, Timothy L. J. (IEEE, 2016)
The purpose of this paper was to develop and validate a new theoretically based scale to measure students' learning of systems thinking in relation to the affective domain in the context of systems engineering education. Two variant questionnaires are reported here, one using only questions constructed using positive grammar and the other using a mix of positive and negative constructs, each applied to a different sample. The first group of 186 participants completed the positive version of the questionnaire, and, the second group of 163 completed the mixed version. Construct validity was examined through exploratory factor analysis (EFA) and confirmatory factor analysis (CFA). EFA was conducted to find the factors underlying each questionnaire. CFA was conducted to confirm the better questionnaire version and to confirm the factors which underlie both versions. The results indicate that a three factor, 16 item, scale with a mix of positive and negative wording is the better instrument with which to measure students' engagement with systems thinking. The results also indicate that the three factor, 16 item construct is a better representative of both versions of the questionnaire, whether the questionnaire has only positive questions or a mix of positive and negative questions.